INNOVATIVE APPROACHES TO THE PROCESS OF FORMATION OF CREATIVE PROFESSIONAL SKILLS OF FUTURE TEACHERS - T.V. Zakharchuk (Academy of Cognitive and Natural Sciences, 2009)
The article covers the problem of forming of creative professional abilities of future teachers; opens up using the innovative methods of teaching, the pedagogical terms of forming of creative activity of future teacher are summarized.